Concept mapping in evaluation practice and theory: A synthesis of current empirical research. - Rizzo Michelin, Linda L. (University of Ottawa (Canada), 1998)
Concept mapping is a conceptualization process that can be used by individuals and groups to develop conceptual frameworks which can guide evaluations and planning (Trochim, 1989). In research, these processes display individual and group representations of concepts about particular domains, illustrating potential relationships among them (Miles, 1994). Cognitive mapping processes involve the acquisition, store, access and utilization of spacial knowledge (Golledge, 1986). Empirical research using concept mapping technology has proliferated within the past fifteen years. Investigation of this research has revealed the existence of a wide variation of domains of inquiry and applications of concept mapping. Using non-traditional meta-analytic research techniques employed in prior reviews by Cousins and associates (Cousins, 1996; Cousins & Earl, 1992; Cousins & Leithwood, 1986; Ross, in press) and others (e.g., Leithwood & Montgomery, 1982), the empirical research studies are explored with relevance to evaluation theory and practice. Emphasis on concept mapping process variations and use in evaluation is ordered. This study provides researchers and evaluators with valuable empirical basis from which to make choices regarding selection and applications of concept mapping.
Keywords: Education, Tests and Measurements.